Zalety stosowania połączonych metod badawcz ych w analizie interakcji na lekcjach jęz yka obcego - Łęska, Krystyna (Neofilolog, 2010)
Numerous studies conducted during language lessons aim at gaining more knowledge about classroom interaction and its relationship with the learning and teaching processes. Early research concerning classroom interaction involved quantitative methodology and was based on some predetermined sets of categories used for coding specific classroom behaviours. However, such an analysis is not sufficient since it does take into consideration whole stretches of the context in which the utterance is produced and does not allow judgements connected with the classroom atmosphere to be made. One way of dealing with these problems is to employ qualitative methods. Recently, there is another tendency in research methodologies, namely, to use a combination of quantitative and qualitative studies (mixed methods research). The article presents an example of an interaction analysis conducted in foreign language classrooms with the help of mixed methods research, which allowed a better understanding of the phenomena that take place during a foreign language lesson.